2007
DOI: 10.1177/104063870701900206
|View full text |Cite
|
Sign up to set email alerts
|

Serological Prevalence of Canine Respiratory Coronavirus in Southern Italy and Epidemiological Relationship with Canine Enteric Coronavirus

Abstract: Abstract. Canine respiratory coronavirus (CRCoV) has been detected in dogs suffering from respiratory disease and is thought to be involved in canine infectious respiratory disease (CIRD) complex. Canine enteric coronavirus (CECoV) is a widespread pathogen of dogs, responsible for mild to severe diarrhea in pups. The purpose of this study was to establish the seroprevalence of CRCoV in Italy and its relationship to CECoV type II seroprevalence. The age and year of sample collection from seropositive dogs was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 16 publications
6
38
2
Order By: Relevance
“…Previous publications have collectively demonstrated the global distribution of CRCoV and its association with respiratory disease in dogs under field conditions (Erles et al, 2003;Decaro et al, 2007;Kaneshima et al, 2006;Priestnall et al, 2006Priestnall et al, , 2007Yachi and Mochizuki, 2006;Knesl et al, 2009). This is the first publication to report experimental infection of dogs using CRCoV, and the comparison of different CRCoV isolates from wide geographic origins.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Previous publications have collectively demonstrated the global distribution of CRCoV and its association with respiratory disease in dogs under field conditions (Erles et al, 2003;Decaro et al, 2007;Kaneshima et al, 2006;Priestnall et al, 2006Priestnall et al, , 2007Yachi and Mochizuki, 2006;Knesl et al, 2009). This is the first publication to report experimental infection of dogs using CRCoV, and the comparison of different CRCoV isolates from wide geographic origins.…”
Section: Discussionmentioning
confidence: 77%
“…Crucially, isolation of CRCoV was achieved from six of the seven tissues collected (the bronchial lymph node remained negative) as well as the lung lavage fluid. Re-isolation of virus from experimentally infected dogs displaying clinical signs of disease, signifies a causal relationship between CRCoV and respiratory disease, which until now has been best demonstrated through epidemiological surveys (Erles et al, 2004(Erles et al, , 2003Decaro et al, 2007;Kaneshima et al, 2006;Priestnall et al, 2006Priestnall et al, , 2007Knesl et al, 2009).…”
Section: Cross Serum Neutralisation Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus appears to be particularly prevalent in housed populations and within 3 weeks of entry to a kennel, dogs develop antibodies to the virus (Erles et al, 2003). Serological evidence of the virus exists in three continents (Decaro et al, 2007;Kaneshima et al, 2006;Priestnall et al, 2006Priestnall et al, , 2007, however little is known regarding the pathogenesis of the infection and the possible role of the virus in the canine infectious respiratory disease (CIRD) complex.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis places CRCoV in group 2 of the Coronaviridae family related most closely to bovine coronavirus (BCoV) and human coronavirus OC43 (OC43) (Erles et al, 2003). Serological studies have shown CRCoV to be present in the UK, Ireland, Italy, USA and Japan (Decaro et al, 2007;Erles and Brownlie, 2005;Kaneshima et al, 2006;Priestnall et al, 2006Priestnall et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%